The co-expressing D1–D2 neurons in the striatum of the common tree shrew (Tupaia glis) - Quiggins, Ranida; Seeharach, Kewalee; Chaisuksunt, Vipavadee; Phasukdee, Noppadol; Yasanga, Thippawan; Bickford, Martha E. (Biomedical Sciences and Clinical Medicine, 2017)
Abstract The striatum contains D1 and D2 neurons within the striosome and matrix regions. The objective of this study was to identify the distribution of D1 and D2 striatal neurons in tree shrews by fluorescent immunohistochemistry using D1, D2 and substance P antibodies. Animal brain sections were immunolabeled with antibodies against the D1 receptor and substance P and then counterstained for nuclei with DAPI. It was revealed that 91% of D1 labeled neurons in the striatum were in close contact with substance P labeled terminals. Thus, substance P antibody was used as a marker for D1 neurons. Brain sections were incubated with antibodies against substance P and D2 receptors and then counterstained for nuclei with DAPI. The results showed that 88% of total neurons were in cotse contact with substance P labeled terminals in the striosome and 30% were D2 labeled neurons that were in contact with substance P labeld terminals. The matrix contained 98% of D2 labeled neurons, and 29% of D2 labeled neurons that were in close contact with substance P labeled terminals. In conclusion, approximately 30 % of striatal neurons in either the striosome or matrix expressed both D1 and D2 receptors. These co-expressing D1-D2 neurons probably send different outputs from those of D1 or D2 neurons.